The oncolytic avian reovirus p17 protein suppresses invadopodia formation via disruption of TKs5 complexes and oncogenic signaling pathways - Hsu, Chao-Yu; Li, Jyun-Yi; Huang, Wei-Ru; Liao, Tsai-Ling; Wen, Hsiao-Wei; Wang, Chi-Young; Lye, Lon-Fye; Nielsen, Brent L.; Liu, Hung-Jen (Frontiers in cellular and infection microbiology, 2025)
Avian reovirus (ARV) is an oncolytic virus that induces autophagy and apoptosis in cancer cells, modulates the immune response, and exposes tumor-associated antigens to the immune system, making it a promising candidate for cancer therapy. Cancer cell migration and invadopodia formation are essential processes in metastasis, and targeting these mechanisms could be beneficial in limiting cancer progression. This study investigated the effects of ARV p17 protein on cancer cell migration and invadopodia formation in HeLa and A549 cell lines. Molecular assays were conducted to examine the expression and interactions of key signaling molecules, including nucleoporin Tpr, p53, PTEN, FAK, Src, Rab40b, PI3K, Akt, TKs5, and Nck1. Analysis of TKs5, Nck1, and Rab40b mRNA levels by quantitative real-time RT-PCR. Furthermore, invadopodia detection, gelatin degradation assay, and Fluorescence imaging was performed to visualize invadopodia structures and assess extracellular matrix degradation. Additionally, rescue experiments were performed by co-transfecting cells with mutant PTEN (C124A), TKs5, or Rab40b plasmids to confirm their roles in mediating the effects of p17. p17 suppressed nucleoporin Tpr, resulting in the activation of p53 and upregulation of PTEN. This blocked the formation of the FAK-Src complex and inhibited the Rab40b-PI3K-Akt signaling pathway. p17 also transcriptionally downregulated TKs5, Nck1, and Rab40b, thereby reducing the formation of TKs5-Nck1 and TKs5-Rab40b complexes, which are critical for invadopodia formation. Fluorescence imaging confirmed a marked reduction in invadopodia formation and matrix degradation in cells expressing p17. Restoration of invadopodia formation upon co-transfection with mutant PTEN, TKs5, or Rab40b confirmed that these molecules are key mediators of p17's inhibitory effects. ARV p17 inhibits cancer cell migration and invadopodia formation by activating the p53-PTEN pathway and suppressing essential signaling and scaffolding complexes (FAK-Src, Rab40b-PI3K-Akt, TKs5-Nck1, and TKs5-Rab40b). These findings suggest that p17 plays a crucial anti-metastatic role and may serve as a novel therapeutic agent for targeting invasive cancer cells.